Evaluation of Risk Factors for Mortality in Febrile Neutropenia - Sabahat Ceken; Habip Gedik; Gulsen Iskender; Meryem Demirelli; Duygu Mert; Goknur Yapar Toros; Tugce Nur Yigenoglu; Fevzi Altuntas; Berna Oksuzoglu; Mustafa Ertek (Journal of Infection in Developing Countries)
Introduction: We aimed to evaluate the epidemiology of infections and factors associated with mortality in patients with febrile neutropenia (FEN).